Expression of estrogen receptor α variants and c-Fos in rat mammary gland and tumors. Issue 199 (May 2020) - Gutiérrez, Alicia; Sambuco, Lorena; Álvarez, Laura; Núñez, Mariel; Bergoc, Rosa; Zotta, Elsa; Martín, Gabriela; Randi, Andrea
Highlights: Nuclear c-Fos increases and ERα46/ERα66 was below 1 in carcinogenic transformation. Nuclear c-Fos was negatively associated to ERα46/ERα66 as tumor grade increases. ERα46 could be inhibitory on mammary gland proliferation, but it is not clear for tumors. In mammary tumors, ERα46 was the predominant isoform. p-Y537-ERα66 and ERK1/2 levels are associated with AP-1 content and proliferation Abstract: Breast cancer is currently the leading cause of cancer death among women worldwide. AP-1 (c-Fos/c-Jun) is associated with proliferation and survival, while cytoplasmic c-Fos activates phospholipid synthesis in cells induced to differentiate or grow. Estrogen receptor α 46 (ERα46) is a splice variant of full-length ERα66 and it is known that it has an inhibitory role in cancer cell growth. We investigated c-Fos localization, its relationship to AP-1, the non genomic pathway of phospho-Tyr537-ERα66, as well as ERα46 and ERα66 isoforms in rat mammary gland development and carcinogenic transformation, and in mammary tumors. Female rats were injected: a) saline solution (Control mammary gland, CMG) or b) N-Nitroso -N- methyl urea (NMU), and samples were taken at 60, 90, 120 and 150 days of life. In addition, we analyzed hormone-dependent (HD) and independent (HI) tumors in ovariectomized rats, and intact tumors (IT) in non-ovariectomized ones. Our results show that, in CMG, nuclear c-Fos and proliferation decreased with age, AP-1 content was low, and nuclear ERα46/ERα66 ratio was higher than 1. In NMU, nuclear c-Fos and proliferation increased with carcinogenic transformation, AP-1 content was high, and nuclear ERα46/ERα66 was below 1. As tumor grade increased, proliferation, nuclear c-Fos and AP-1 expression were negatively associated to nuclear ERα46/ERα66 in IT. In HD, nuclear ERα46/ERα66, nuclear c-Fos expression, AP-1 levels and proliferation were lower than in HI, whose growth is estrogen-independent. Phospho-Tyr537-ERα66 content and ERK1/2 activation were associated with AP-1 levels and cell proliferation. Collectively, our findings support the notion that variant detection and ERα46/ERα66 ratio could shed light on the role of ERα isoforms in mammary gland transformation and the behavior of ERα positive mammary tumors.